Prevention of Major Accidents of Mobile Risk Sources - Katarína Mäkká; Katarína Kampová; Jacek Dworzecki (Communications - Scientific letters of the University of Zilina, 2021)
At present, the issue of public safety in the production and manipulation of hazardous chemicals deserves more attention, since various major accidents such as fires, explosions and toxic gas releases take place frequently. The issue of prevention of emergency events has become more and more topical. The growing amount of hazardous substances transported leads to increased risk of emergencies. In order to reduce this risk in the transport of hazardous substances, a number of technical, operational, traffic and safety conditions and requirements must be fulfilled. These all contribute to the reduction of hazards and risks. The aim of the presented article was to determine the extent of the danger zone in the event of a gasoline leak due to a traffic accident in a built-up urban area with a high frequency of traffic and population movement.